2021
DOI: 10.3390/microorganisms9091840
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility, Minimum Inhibitory Concentrations, and Clinical Profiles of Stenotrophomonas maltophilia Endophthalmitis

Abstract: Stenotrophomonas maltophilia has been reported in various ocular infections, including keratitis, conjunctivitis, preseptal cellulitis, and endophthalmitis, all of which may lead to vision loss. However, the S. maltophilia strain is resistant to a wide variety of antibiotics, including penicillins, third-generation cephalosporins, aminoglycosides, and imipenem. In this study, we retrospectively reviewed the clinical characteristics, antibiotic susceptibility, antimicrobial minimum inhibitory concentrations (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In severe cases, hormone supplementation may be necessary. This investigation revealed that levofloxacin, moxifloxacin, and gatifloxacin had favourable susceptibility against Staphylococcus, Streptococcus, Enterobacteriales, and Pseudomonas, while Stenotrophomonas maltophilia exhibited susceptibility rates below 50% [ 43 , 44 ]. Hence, it is imperative to base treatment decisions on the outcomes of susceptibility tests.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases, hormone supplementation may be necessary. This investigation revealed that levofloxacin, moxifloxacin, and gatifloxacin had favourable susceptibility against Staphylococcus, Streptococcus, Enterobacteriales, and Pseudomonas, while Stenotrophomonas maltophilia exhibited susceptibility rates below 50% [ 43 , 44 ]. Hence, it is imperative to base treatment decisions on the outcomes of susceptibility tests.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [ 29 ] collected S. maltophilia isolates from 21 patients with culture-proven keratitis; all collected isolates were susceptible to levofloxacin and moxifloxacin. Our previous study [ 18 ] revealed that levofloxacin as well as moxifloxacin were susceptible to S. maltophilia in 67% of isolates, and the MIC 90 values were lowest for the S. maltophilia isolates in comparison with other antimicrobial agents (1, 8, and 12 µg/mL for levofloxacin, moxifloxacin, and gatifloxacin, respectively) from isolates from endophthalmitis. In the present study, the fluoroquinolones were over 90% susceptible for S. maltophilia isolates in both the disk diffusion test and the E-test.…”
Section: Discussionmentioning
confidence: 99%
“…It was used to determine the susceptibility of antimicrobials and found the potential treatment for microorganisms. As far as we were aware, reports on the antibiotic MICs for S. maltophilia isolates collected from other ocular infections are rare, and whether the MICs for such isolates are similar to those for endophthalmitis isolates is unclear [ 18 , 19 ]. Accordingly, the aim of the present study was to investigate the antibiotic susceptibility—analyzed using MICs—of S. maltophilia isolates collected from patients with ocular infections over a 10-year period.…”
Section: Introductionmentioning
confidence: 99%